Social Harmony of Society as a Source of Politeness Learning for Elementary School Students - Fitria Purnamasari; Sukartono; Fitri Puji Rahmawati; Minsih; Choiriyah Widyasari (Jurnal Ilmiah Sekolah Dasar, 2022)
The problem encountered in this study is the lack of politeness character education in students which causes a lack of student politeness. The purpose of this study is to analyses the form of adherence to the principle of politeness in language that comes from the social harmony of the community which can be used as a source of learning politeness for elementary school students. This research uses qualitative research. The research design is a case study. The resource persons in this study were village heads, school principals, and teachers. In this study, the data collection techniques used was observation and interview techniques. In this study, researchers used triangulation to test the validity of the data, namely technical triangulation, and source triangulation. This research was conducted using interactive data analysis techniques, namely data collection, data reduction, data presentation, and concluding. The results showed that the language attitude of people was polite and could be used as a source of learning politeness for elementary school students. The implementation of politeness learning resources that come from the social harmony of the community is obtained from the kenduri tradition.